GURU PROFESIONAL - Abdul Hamid (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2017)
Master is a person who is so well respected for having a considerable contribution to the success of learning in school. Teachers play a role in helping the development of learners to achieve optimal ability. When parents enroll their children at every level of education at a particular school, at that time he also put great expectations on the teacher, so that children can get education, coaching and learning and guidance so that the child can develop optimally. Interest, talent, ability and potential of learners will not develop optimally without the help of teachers. In this regard, teachers need to pay attention to students individually. Teacher tasks not only teach but also educate, nurture, guide and shape the personality of students to prepare and develop resources owned by each learner. So great the task and responsibilities of teachers, so it takes attitude and behavior that can be a role model for children. Professional teachers should make students as learning partners because their hope is to be a moral, creative and innovative person to achieve his goals. Keywords: Professional Teachers